Association between sleeping patterns, oral hygiene status, and self-reported academic performance among dental students - Khanal, Sunita; Shrestha, Sujita; Bhattarai, Rosina (Journal of Kathmandu Medical College, 2021)
Background: Sleep is very important for normal functioning and overall development of the body for all. Information on association between sleeping patterns, oral hygiene status, and self-reported academic performance among dental students is not available in Nepal. Objectives: The aim of the study was to assess the association between sleeping patterns, oral hygiene status, and selfreported academic performance among dental students. Methods: Analytical cross-sectional study was conducted among second year to final year students of Kantipur Dental College for a period of four months. Ethical approval was obtained from the institutional review committee of Kantipur Dental College before collecting the data. Convenience sampling was used. Data collection was done by using self administered, Pittsburgh Sleep Quality Index (PSQI) questionnaire for assessing sleep quality. For assessing oral hygiene status, Greene and Vermillion OHI-S index was used. Academic performance was measured by the performance of the students in their previous university exam. Data were entered in Microsoft Excel and analysis was done by using SPSS version 20 and p <0.05 was considered to be statistically significant. Results: Altogether 138 students participated in the study. Self-reported sleep quality was fairly good among 82 (59.4%) students but the actual sleep quality determined by PSQI was good among 92 (67 %) students. Mean hours of actual sleep of participants was 7 ± 1.52 hours. The association between sleeping patterns, academic performance, and oral hygiene status was found to be statistically insignificant. Conclusion: The sleeping patterns, oral hygiene status and academic performance had no significant association.